Comparative Study on Effects of 2% Lidocaine Hydrochloride with Adrenaline (1:200000) on Blood Pressure Among Controlled Hypertensive and Nonhypertensive Patients During Dental Anesthesia - Tuladhar, Lujaw Ratna; Budhathoki, Meen Bahadur; Bhattarai, Anjali; Bimb, Kushal; Acharya, Nikhil; Tuladhar, Eans Tara (Journal of Lumbini Medical College, 2021)
Introduction: Local anesthetic used for dental extraction is 2% lidocaine hydrochloride with adrenaline (1:200000). Lidocaine is cardiac depressant and adrenaline is cardiac stimulant; it decreases or increases blood pressure respectively. Methods: A total of 100 patients (50 controlled hypertensive and 50 non-hypertensive) were selected. The study was conducted over a period of 14 months from January 2020 to February 2021. Blood pressure was measured for patients who were planned for dental extraction by auscultatory method. Following that, 1.5-3 ml (depending upon the nerve block) 2% lidocaine with adrenaline (1:200000) was injected using 3ml syringe (26 Gauge). Blood pressure was re-recorded after 10 minutes from the time of injection. Visual analog scale pain score was obtained during administration of local anesthesia. Paired t-test was applied to compare blood pressure change before and after administration of local anesthesia in controlled hypertensive and non-hypertensive patients. Results: There was a statistically significant increase in both systolic and diastolic blood pressure in non-hypertensive patients (p = 0.008, p = 0.017). This, however, was not the case with controlled hypertensive patients. There was statistically significant increase in systolic blood pressure (p < 0.001). Pain on injection (50% in non-hypertensive and 48% in controlled hypertensive patients) was the only adverse drug reaction that was reported in both groups. Conclusion: 2% lidocaine hydrochloride with adrenaline (1:200000) increased systolic but not diastolic blood pressure in controlled hypertensive patients.